2012
DOI: 10.2478/v10213-012-0051-z
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Selected Genes in Campylobacter Jejuni and Campylobacter Coli Isolates from Domestic Animals

Abstract: In the present study, the presence of flaA, cadF, cdtB, and iam genes of Campylobacter sp. were analysed using PCR. Material for analyses comprised 100 Campylobacter sp. isolates obtained from healthy broiler chickens, fatteners, and calves, among which 84 isolates were ascribed to Campylobacter jejeuni and 16 to Campylobacter coli. All isolates (100%) had the cadF gene responsible for adhesion and the flaA gene determining the motility of the analysed bacteria. The frequency of occurrence of the cdtB gene res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
(9 reference statements)
0
8
1
Order By: Relevance
“…Biswas et al (2011) confirmed the occurrence of this gene in 100% of the examined C. jejuni strains derived from human clinical studies and cow faeces. Selwet and Galbas (2012a;2012b) observed that the cadF and flaA genes were found in 100% of C. coli and C. jejuni isolated from broilers, porkers, calves and piglets. All the strains of C. jejuni, C. coli C. upsaliensis under analysis carried the cdtB gene encoding the protein exhibiting toxic properties, i.e.…”
mentioning
confidence: 99%
“…Biswas et al (2011) confirmed the occurrence of this gene in 100% of the examined C. jejuni strains derived from human clinical studies and cow faeces. Selwet and Galbas (2012a;2012b) observed that the cadF and flaA genes were found in 100% of C. coli and C. jejuni isolated from broilers, porkers, calves and piglets. All the strains of C. jejuni, C. coli C. upsaliensis under analysis carried the cdtB gene encoding the protein exhibiting toxic properties, i.e.…”
mentioning
confidence: 99%
“…According to the investigations by Andrzejewska et al (2011) and Selwet and Galbas (2012a;2012b) on C. coli occurrence in people, dogs, cats, and piglets, the presence of the flaA gene in all the examined isolates was also recorded (Selwet et al, 2015). The next factor affecting virulence is gene cadF, which is responsible for production of adhesines.…”
Section: T H I S C O P Y I S F O R P E R S O N a L U S E O N L Y -D Imentioning
confidence: 98%
“…In the experiments, the cadF gene was found also in 100% of isolates from both study groups. Some researchers attribute a high importance of the cadF gene leading to campylobacteriosis in human (Selwet and Galbas, 2012a). Cytokines such as interleukin-8 (IL-8) are secreted by host cells in response to bacterial invasion, acting as early warning signs to the host immune system, and Campylobacter spp.…”
Section: T H I S C O P Y I S F O R P E R S O N a L U S E O N L Y -D Imentioning
confidence: 99%
See 1 more Smart Citation
“…Thermotolerant bacteria of the Campylobacter genus (mainly Campylobacter jejuni and Campylobacter coli) are part of the natural intestinal flora of birds and mammals. They are also commonly found in water and soil contaminated with animal faeces [1]. Contact with faeces or with a sick animal and failure to comply with basic rules of hygiene may cause campylobacteriosis in humans [2].…”
Section: Introductionmentioning
confidence: 99%